Heat Shock Protein 40 (HSP40) in Pacific White Shrimp (Litopenaeus vannamei): Molecular Cloning, Tissue Distribution and Ontogeny, Response to Temperature, Acidity/Alkalinity and Salinity Stresses, and Potential Role in Ovarian Development - Chen, Ting; Lin, Tiehao; Li, Hongmei; Lu, Ting; Li, Jiaxi; Huang, Wen; Sun, Hongyan; Jiang, Xiao; Zhang, Jiquan; Yan, Aifen; Hu, Chaoqun; Luo, Peng; et al. (Frontiers in Physiology, 2018)
Heat shock proteins (HSPs), a family of conserved proteins that are produced by cells in response to stresses, are known as molecular chaperones with a range of housekeeping and cellular protective functions. The 40 kD heat shock protein (HSP40) is a co-chaperone for HSP70 in the regulation of ATP hydrolysis. Unlike its well-documented cofactor HSP70, little is currently known regarding the biological functions of HSP40 in crustacean species such as penaeid shrimp. In the present study, the cDNA encoding HSP40 (Lv-HSP40) was identified from the Pacific white shrimp Litopenaeus vannamei, a highly significant commercial culture species. The structural organization indicates that Lv-HSP40 belongs to the type-I HSP40s. The muscle, gill, and hepatopancreas are the main sites of Lv-HSP40 transcript expression. Within these tissues, Lv-HSP40 mRNA were predominantly exhibited in the myocytes, epithelial cells and hepatopancreatic cells, respectively. Under acute thermal stress in the culture environment, Lv-HSP40 transcript levels are significantly induced in these three tissues, while low pH stress only upregulates Lv-HSP40 mRNA in the hepatopancreas and gill. During ontogenesis, Lv-HSP40 transcript levels are high at early embryonic stages and drop sharply at late embryonic and early larval stages. The ovary is another major organ of Lv-HSP40 mRNA expression in female shrimp, and Lv-HSP40 transcripts were mainly presented in the follicle cells but only weekly detected in the oocytes. Ovarian Lv-HSP40 mRNA levels increase continuously during gonadal development. Silencing of the Lv-HSP40 gene by RNA interference may effectively delay ovarian maturation after unilateral eyestalk ablation. The roles of Lv-HSP40 in ovarian development are speculated to be independent of its cofactor HSP70, and the vitellogenesis factor vitellogenin (Vg) and vitellogenin receptor (VgR). Our study, as a whole, provides new insights into the roles of HSP40 in multiple physiological processes in L. vannamei: (1) HSP40 is a responding factor during stressful conditions; and (2) HSP40 participates in embryonic and ovarian development.